DEVELOPMENT OF LACIDIPINE TRANSFEROSOMAL FORMULATIONS FOR TRANSDERMAL DELIVERY: IN VIVO CHARACTERIZATION IN RATS - DUNAKA, SARITHA; JANAPAREDDI, KRISHNAVENI (International Journal of Applied Pharmaceutics, 2025)
Objective: Lacidipine is a calcium channel blocker prescribed to treat hypertension. Due to first-pass metabolism, the drug has low bioavailability via oral route. The present research aims to enhance bioavailability by developing lacidipine-loaded transferosomes for transdermal delivery and evaluate their efficacy in a rat model. Methods: Transferosomes were prepared by thin film hydration technique and characterized for physicochemical properties. Permeation studies across rat skin were carried out using Franz diffusion cells. Pharmacodynamic and Pharmacokinetic studies were conducted on male Wister rats. The optimized transferosomal formulation (F3L) contains soya lecithin, tween 80 and drug in proportion of 85:15:4 with labrasol (2%) as permeation enhancer. Results: The optimized formulation exhibited a vesicle size of 132.6 nm, Polydispersity index (PDI) of 0.174, zeta potential of-33.7 mV and entrapment efficiency 97.5%. The steady-state flux of optimized formulation (F3L) and drug suspension was 83.1µg/cm2/h and 16.9 µg/cm2/h, respectively. The flux of F3L was significantly high (P<0.0001,4.92 times) compared with drug suspension. Scanning electron microscopic images showed spherical-shaped transferosomes. The antihypertensive activity was carried out in fructose-induced rats by tail cuff method. The transferosomal formulation F3L significantly decreased systolic blood pressure (P<0.0001) compared to an oral drug suspension. The antihypertensive effect of transdermal formulation was sustained for up to 24 h. The bioavailability of optimized transferosomal formulation was 3.37 folds compared to oral lacidipine suspension. The histopathological study confirmed the safety of transferosomes. Conclusion: The results confirmed the potential advantage of employing transferosomes as suitable nanocarriers for the transdermal delivery of lacidipine.